1978
DOI: 10.2466/pr0.1978.42.1.219
|View full text |Cite
|
Sign up to set email alerts
|

The Behavioral Target Complaints Form: A Nonreactive Measure of Psychotherapeutic Outcome

Abstract: To determine whether or not goal setting could be a sensitive measure of outcome clients set specific behavioral goals on the Behavioral Target Complaints Form and then evaluated their progress after seven 1-hr. sessions of psychotherapy. The sample consisted of 20 university and community clients treated with brief therapy by seven advanced graduate students and one faculty member. The 10 clients who set goals did not show greater improvement than the 10 who did not set goals on either of two other measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
1985
1985

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Methodologically, the question of measurement confounding due to multiple reassessments during psychotherapy was tested in addition to Burton and Nichols’s (1978) assessments, which were done only at the beginning and conclusion of treatment. No differences in subjects were found when comparing simple pre- and postmeasurements with multiple reassessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methodologically, the question of measurement confounding due to multiple reassessments during psychotherapy was tested in addition to Burton and Nichols’s (1978) assessments, which were done only at the beginning and conclusion of treatment. No differences in subjects were found when comparing simple pre- and postmeasurements with multiple reassessments.…”
Section: Discussionmentioning
confidence: 99%
“…The current study had as an ancillary consideration a possible methodological problem. Burton and Nichols (1978) warned that if defining target symptoms itself is therapeutic, "then studies of therapy with goal-setting as an outcome measure are in fact evaluating treatment plus goal-setting rather than just treatment" (p. 221). These authors found, however, that administering target complaints at the first and last sessions (Weeks 1 and 7 in their study) did not influence outcome assessment compared with a no-target-complaints control group.…”
mentioning
confidence: 99%